A series of two cases of rare tumors: Solitary fibrous tumor of the pleura - Bukamur, Hazim (Respir Med Case Rep, 2019)
Solitary fibrous tumors of the pleura (SFTPs) are rare neoplasms of mesenchymal origin most commonly arising in the pleura and have a benign biological behavior in the majority of cases. Most patients with SFTPs are asymptomatic; however, symptoms are mostly related to the mass effect within the thoracic cavity. Chest computed tomography (CT) scanning is the radiographic test of choice, but findings lack specificity. Surgical resection is the treatment of choice for most patients. Long-term survival after resection of benign SFTPs is excellent. In this case series, we present two females, one presented with shortness of breath (SOB) and nonproductive cough and the other one was referred because of abnormal x-ray findings. The histological as well as the immunohistochemical examination revealed the mass to be a solitary fibrous tumor of the pleura.